2D to 2.5D transitions through controlled swelling delamination of hydrogel microstructures - Ha Cheol Woo; Dupont Maxime; Kim Jongsu; Choi Jae Won; Lee Ji-Sun; Han Jisu; Yeon Si-Mo; Son Yong; Cheng Xiangming; Edavalath Hritwik N.; Prabhakaran Prem (Materials & Design, 2021)
Hydrogel precursor photoresists (HPR) are being studied widely due to the close similarities between HPR cured microstructures and biological materials. A vast majority of such resists are formulated in water and suffer from swelling-related inhomogeneities during microfabrication. Hence formulation HPRs in non-aqueous media are being studied as an alternative. This approach enables controlled swelling of fabricated structures. In this work, we demonstrate that controlled swelling of hydrogel microstructures fabricated by two-photon lithography (TPL) can be used to drive 2D to 2.5D transitions in flat microstructures. Through fabrication experiments, mechanical analysis and finite element method (FEM) simulations we have shown that swelling delamination leads to bend microstructures, and the height of the resulting bend structure depends on the designed thickness of the structure.